- #1

- 552

- 18

Is [tex]\frac{∂y}{∂x}×\frac{∂x}{∂z}=-\frac{∂y}{∂z}[/tex]?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter tade
- Start date

- #1

- 552

- 18

Is [tex]\frac{∂y}{∂x}×\frac{∂x}{∂z}=-\frac{∂y}{∂z}[/tex]?

- #2

CompuChip

Science Advisor

Homework Helper

- 4,302

- 47

No, the chain rule does not involve such a minus sign.

Why are you asking?

Why are you asking?

- #3

arildno

Science Advisor

Homework Helper

Gold Member

Dearly Missed

- 9,970

- 134

In these cases, it is true that we have the counter-intuitive result:

[tex]\frac{\partial{Y}}{\partial{x}}\frac{\partial{X}}{\partial{z}}\frac{\partial{Z}}{\partial{y}}=-1[/tex]

- #4

arildno

Science Advisor

Homework Helper

Gold Member

Dearly Missed

- 9,970

- 134

Consider the function G(x,y,z)=x+y+z

Now, the condition G(x,y,z)=0 gives rise to the equation x+y+z=0

We may now form three separate function definitions:

X(y,z)=-y-z

Y(x,z)=-x-z

Z(x,y)=-x-y

We have now that:

G(X(y,z),y,z)=-y-z+y+z=0, i.e, the condition G=0 is satisfied IDENTICALLY, for all choices of y and z.

Similarly with the other two substitutions.

We see that in this case, that we have:

[tex]\frac{\partial{Y}}{\partial{x}}=\frac{\partial{X}}{\partial{z}}=\frac{\partial{Z}}{\partial{y}}=-1[/tex]

and therefore,

[tex]\frac{\partial{Y}}{\partial{x}}\frac{\partial{X}}{\partial{z}}\frac{\partial{Z}}{\partial{y}}-1[/tex]

- #5

- 552

- 18

Try using the simple example z = x + yNo, the chain rule does not involve such a minus sign.

Why are you asking?

Isn't there a minus sign?

- #6

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 963

- #7

- 552

- 18

Is there a general formula for partial derivatives or is it a collection of several formulas based on different conditions?

Anyway, consider a function w ( x, y, z ). We can then derive z ( x, y, w ).

In this case, is

[tex]\frac{∂w}{∂z}×\frac{∂z}{∂x}=-\frac{∂w}{∂x}?[/tex]

- #8

arildno

Science Advisor

Homework Helper

Gold Member

Dearly Missed

- 9,970

- 134

"w ( x, y, z ). We can then derive z ( x, y, w )."

This is meaningless.

This is meaningless.

Share: